La mise en ligne des informations liées aux risques - Anne Peltier; Mathieu Vidal; Sylvia Becerra (Netcom)
This paper addresses the risks associated with modelling flood hazards. It questions whether the provision of such information online can constitute a real tool of prevention or is potentially only a useful alibi for public authorities.